2011
DOI: 10.1373/clinchem.2010.151845
|View full text |Cite
|
Sign up to set email alerts
|

Direct Serum Assay for MicroRNA-21 Concentrations in Early and Advanced Breast Cancer

Abstract: BACKGROUND: MicroRNAs (miRs) are a class of small noncoding RNAs whose expression changes have been associated with cancer development and progression. Current techniques to isolate miRs for expression analysis from blood are inefficient. We developed a reversetranscription quantitative real-time PCR (RT-qPCR) assay for direct detection of circulating miRs in serum. We hypothesized that serum concentrations of miR-21, a biomarker increased in breast tumors, would correlate with the presence and extent of breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
285
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(306 citation statements)
references
References 34 publications
20
285
1
Order By: Relevance
“…Serum miR-21 was also found to be significantly higher in patients with hepatocellular carcinoma (HCC) than in healthy controls (Xu et al, 2011). Asaga et al found that serum miR-21 has diagnostic and prognostic potential in breast cancer (Asaga et al, 2011). In Zheng's study, patients with gastric cancer display a significantly higher level of miR-21 in peripheral blood than those from controls.…”
Section: Discussionmentioning
confidence: 96%
“…Serum miR-21 was also found to be significantly higher in patients with hepatocellular carcinoma (HCC) than in healthy controls (Xu et al, 2011). Asaga et al found that serum miR-21 has diagnostic and prognostic potential in breast cancer (Asaga et al, 2011). In Zheng's study, patients with gastric cancer display a significantly higher level of miR-21 in peripheral blood than those from controls.…”
Section: Discussionmentioning
confidence: 96%
“…Knocking down its expression could attenuate its contribution in the cancer process. Recent studies also found high levels of miR-21 in breast cancer patient serum (Wang et al, 2010;Asaga et al, 2011). Its increased expression can also be detected in a variety of other malignancies including glioblastoma, ovarian cancer, lung cancer, and colorectal cancer (Chan et al, 2005;Yanaihara et al, 2006;Iorio et al, 2007;Schee et al, 2012;Wang and Zhang, 2012), indicating that miR-21 may have diagnostic and prognostic values.…”
Section: Mir-21mentioning
confidence: 92%
“…Since cellular miRNAs play a fundamental role in regulation of a variety of cellular, physiological, and developmental processes, it is easy to understand that their aberrant expression can lead to a variety of human diseases including cancer. A number of cellular miRNAs were shown in fact to be located in fragile regions of the human genome that are associated with cancer (70), and dysregulated miRNAs have been shown to play a crucial role in tumor initiation, progression, and metastasis, and are often associated with diagnosis, prognosis, and response to therapy (71)(72)(73) (Table II). Lu et al developed a method for bead-based miRNA profiling.…”
Section: Cellular and Circulating Mirnas In Neoplastic Diseasesmentioning
confidence: 99%